Hepatitis C prevalence and associated risk factors among individuals who are homeless and diagnosed with mental illness: At Home/Chez Soi Study, Vancouver, BC. (31st July 2018) - Nikoo, Nooshin; Javidanbardan, Sanam; Akm, Moniruzzaman; Hakobyan, Syune; Nikoo, Mohammadali; Kwan, Celia; Song, Michael; Vogel, Marc; Somers, Julian; Krausz, Michael
Abstract: Background: There is scarce evidence on prevalence of hepatitis C virus (HCV) infection among individuals who are homeless and diagnosed with severe mental illness. We aimed to investigate the prevalence of HCV infection and associated risk factors in a representative sample of adults from At Home study. Methods: The Vancouver At Home study is part of the At Home/Chez Soi (AH/CS) project—a pragmatic randomized controlled trial of a Housing First intervention among homeless persons with mental illness in five Canadian cities between 2009 and 2013 with a 2-year follow-up period. Results: Of 497 participants, 28% reported positive HCV serostatus. Educational level equal or less than eighth grade (AOR: 2.3, 95% CI: 1.1, 4.8), history of incarceration (AOR: 2.1, 95% CI: 1.2, 3.5), substance dependence (AOR: 2.0, 95% CI: 1.1, 3.7) and injection drug use during one month prior to the recruitment (AOR: 7.8, 95% CI: 4.0, 15.0) were associated with an increased risk of HCV infection. Having a psychotic disorder (AOR: 0.6, 95% CI: 0.3, 1.0) and age < 25 (AOR: 0.2, 95% CI: 0.0, 0.7) were associated with a lower risk. Blood tests performed on 30 participants agreed with self-report in 97% of cases [Kappa = 0.9 (95% CI: 0.6, 1.3), PABAK = 0.9]. Conclusion: The high prevalence of HCV among individuals who were homeless with mental illness underlies the importance of prevention and treatment of HCV in this population, especially those with concurrent substance use disorders. Self-report seems to be a valid tool for evaluation of the HCV status in this population.